2023
DOI: 10.1128/aac.00035-23
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Diarylquinolines Improve Sterilizing Activity of Regimens with Pretomanid and the Novel Oxazolidinone TBI-223 in a Mouse Tuberculosis Model

Abstract: A regimen comprised of bedaquiline (BDQ, or B), pretomanid, and linezolid (BPaL) is the first oral 6-month regimen approved by the U.S. Food and Drug Administration and recommended by the World Health Organization for the treatment of extensively drug-resistant tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Based on published data suggesting the SPaO regimen, at the doses of, S 12.5 mg/kg; Pa 100 mg/kg; and O 100 mg/kg, is able to eradicate lung infection in Mtb-infected mice by week 6 [36], the relapse time points of 5 and 6 weeks were selected to evaluate the adjunctive sterilizing activity of SnMP. In the current study, we found that, although SnMP increased the bactericidal activity of SPaO, adjunctive therapy did not reduce relapse rates compared to the background SPaO regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on published data suggesting the SPaO regimen, at the doses of, S 12.5 mg/kg; Pa 100 mg/kg; and O 100 mg/kg, is able to eradicate lung infection in Mtb-infected mice by week 6 [36], the relapse time points of 5 and 6 weeks were selected to evaluate the adjunctive sterilizing activity of SnMP. In the current study, we found that, although SnMP increased the bactericidal activity of SPaO, adjunctive therapy did not reduce relapse rates compared to the background SPaO regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we evaluated the adjunctive sterilizing activity of SnMP at different dosages (5 mg/kg and 10 mg/kg) in combination with SPaO. We selected treatment durations expected to yield > 50% relapse rates for the backbone regimen based on the prior literature [36]. The mice were treated for a total of 5 or 6 weeks, at which time the treatment was discontinued, and microbiological relapse was assessed 3 months later (Fig 4A).…”
Section: Snmp Adjunctive Therapy Enhances the Bactericidal Efficacy O...mentioning
confidence: 99%
“…Results published from a mouse TB model suggest that TBAJ‐876 and TBAJ‐587 have even higher potency with potentially lower toxicity, which could lead to an overall shortened duration of drug‐resistant TB treatment due to increased sterilization (Table 3). In the same mouse TB model, TBAJ‐587 and pretomanid administered in combination with a novel oxazolidinone, sutezolid, significantly reduced the relapse rate compared with the linezolid combination 89 . Superior regimens containing novel oxazolidinones and diarylquinolones may improve efficacy and safety in those being treated for MDR‐TB 89 .…”
Section: Updates In Pharmacologic Options For Drug‐resistant Tbmentioning
confidence: 97%
“…In the same mouse TB model, TBAJ-587 and pretomanid administered in combination with a novel oxazolidinone, sutezolid, significantly reduced the relapse rate compared with the linezolid combination. 89 Superior regimens containing novel oxazolidinones and diarylquinolones may improve efficacy and safety in those being treated for MDR-TB. 89 Another new class was created based on analog diarylquinolines, the diarylpyridines, which include:…”
Section: Diarylquinolinesmentioning
confidence: 99%
See 1 more Smart Citation